1999
DOI: 10.1111/j.1151-2916.1999.tb02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for 6‐Coordinated Zirconium in Inactive Nuclear Waste Glasses

Abstract: In inactive glasses used as models for French nuclear waste forms, Zr K-and L 2,3 -edge X-ray absorption spectroscopy spectra indicate that Zr is only 6-coordinated, with d(Zr-O) distances of 2.08 ± 0.01 Å and with a small radial disorder. Beyond, the first coordination shell, next-nearest Si neighbors occur at about 3.4 Å. These distances exclude the presence of [7] Zr and/or [8] Zr and suggest [6] Zr-O-Si angles close to 130°, indicating corner-shared ZrO 6 and SiO 4 polyhedra. This structural configuration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
99
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 17 publications
19
99
0
Order By: Relevance
“…This slightly distorted [ZrO 6 ] octahedral are consistent with experimental observations. [44][45][46] BAD of O-Na-O shows a higher/sharper peak at~60°and a lower/broader peak at 110°for all compositions, which is consistent with a previous study on soda-lime silicate glasses. 53 Interestingly, BADs of O-Ca-O exhibit higher intensity of the peak~60°as compared to the peak~90°.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This slightly distorted [ZrO 6 ] octahedral are consistent with experimental observations. [44][45][46] BAD of O-Na-O shows a higher/sharper peak at~60°and a lower/broader peak at 110°for all compositions, which is consistent with a previous study on soda-lime silicate glasses. 53 Interestingly, BADs of O-Ca-O exhibit higher intensity of the peak~60°as compared to the peak~90°.…”
Section: Discussionsupporting
confidence: 92%
“…The study of Zr in both simplified and simulant borosilicate glasses using EXAFS 44,57,60,61 dates back to the late 1990s and has consistently shown that Zr is in 6-fold coordination, with evidence for 7-fold coordinated Zr only appearing at very high ZrO 2 contents. 61 In contrast, the composition of the second shell has not been unequivocally resolved from EXAFS due in large part to the large number of degrees of freedom (elements, distances, coordination numbers, Debye-Waller factors) in the traditional shell-by-shell EXAFS fitting approach.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum resembles that of BaZrO 3 with a sixfold coordinated Zr 4+ (Dixit et al 2004). Data, mostly X-ray-based, from Zr-bearing silicate glasses have been interpreted to indicate that Zr 4+ is in sixfold coordination with oxygen (Farges et al 1991, Galoisy et al 1999Farges and Rossano 2000). From this limited information, we conclude that Zr 4+ in ZrO 2 - Fig.…”
Section: Raman Spectroscopymentioning
confidence: 92%
“…These techniques complement x-ray diffraction (XRD) measurements. The XANES is able to determine the chemical surrounding (e.g., crystal field, density of unoccupied states, and the orientation of the specimen with respect to the polarization of the photon) 27,28 . Typically, measurements are made in transmission mode if attenuation length of the photon in the material being analysed is sufficiently long; however, in the soft X-ray region, due to small attenuation length, XANES measurements are made by detecting total electron yield (TEY), which is surface sensitive 29 .…”
Section: Introductionmentioning
confidence: 99%